The Availability Of Worship Facilities And Infrastructure At Tangkahan Tourist Site Namo Sialang Village Batang Serangan Sub-District - Khoir Nadaya; Sahdin Hasibuan (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2023)
The purpose of this study was to determine the descriptive condition of the availability of worship facilities and infrastructure at the Tangkahan tourist location, Namo Sialang Village, Batang Serangan District. The research method used is descriptive qualitative. The subjects in this study were the managers of Tangkahan tourist attractions, namely Mr. Ngarihkan Pasaribu as chairman and Mr. Kembaren as vice chairman, as well as 5 people around Namo Sialang Village, Batang Serangan Subdistrict. the data sources used were primary data sources, namely by conducting initial observations and then conducting interviews with the community and also using supporting secondary data. The results of the study are a. Based on the current condition of the area, including damaged road access, potholed pavement, lack of clean water and telecommunications networks, lack of electricity and lighting networks, lack of direction signs and some of them are damaged. no identity gate or welcome board, lack of security facilities, and lack of health facilities, it can be concluded that the availability of tourist facilities in the Tangkahan Nature Tourism area is very inadequate. b. One of the facilities and infrastructure related to sharia is the prayer room. In Tangkahan Nature Tourism, there are few prayer rooms for Muslims to pray, but there are some shortcomings. In Tangkahan Nature Tourism, there is an ablution place for Muslim visitors who want to clean themselves before carrying out their prayers.